Influence of Social Capital on the Development of Agricultural Areas on Highland Peatlands in Humbang Hasundutan Regency - Sipahutar, Tumpal; Nasution, Zulkifli; Purwoko, Agus; Simatupang, Sortha (Budapest International Research and Critics University, 2021)
The objectives of this study are (1) There are several social capitals owned by farmer groups in supporting the development of highland peatland agricultural areas in Dolok Sanggul District. (2) Measuring the level of social capital of farmer groups on highland peatlands in Dolok Sanggul District. (3) Analyzing the relationship between social capital and the development of agricultural areas in the Upland Peatlands in Dolok Sanggul District. The research method used is the interpretation of the logistic regression model to explain the functional relationship between the dependent variable and the independent variable and to define the unit of change in the dependent variable caused by the independent variable. The results of the research obtained that social capital for farmers who manage agricultural land in Dolok Sanggul District includes two interrelated categories, namely the structural category which includes social relations and solidarity, and the cognitive category which includes health, norms, trust and cooperation. Overall the average level of social capital of farmers in the peatlands of Dolok Sanggul District is 70.45% or moderate (>50-75%), where the level of social capital for social relations (75.9%), solidarity (76.1% ), and cooperation (76.5%) included in the high level of social capital (75-100%), while the level of social capital for health (74.3%), norms (64.2%) and trust (55.7%) ) is included in the moderate level of social capital (50-75%). The results of the analysis show that the relationship variable has a significant effect on increasing farmers' income on peatlands in Dolok Sanggul District. Likewise with social relations, the better the social relations between farmers, the higher the opportunity to increase farmers' income.